The effectiveness of hand-body observation and manipulation methods on taekwondo taegeuk learning among primary school children - Kursin, J.; Shapie, M. N. M.; Hakim, M. I. H. M.; Nor, M. A. M.; Taib, M. G.; Linoby, A.; Muhyi, M. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. A good teaching method allows better transfer of knowledge between teachers and students. Problems and aim. Taekwondo instructors lack exposure to the variety of methods of teaching Taekwondo to children makes children not interested in participating in Taekwondo. This study aimed to examine the effectiveness of two teaching methods; observation techniques and hand-body manipulation on Taekwondo Taegeuk 3 (TT3) learning among primary school children. Methods. The design of this study used pre- and post -test experimental research methods. The study population consisted of primary school children. A total of 40 children who are members of a Taekwondo club in Malaysia were involved in this study. All subjects followed the same pre -test session before the intervention session began. Subjects were divided into 2 experimental groups namely N1 = 20 (observation), N2 = 20 (hand-body manipulation) and attended 2 intervention sessions for 3 hours, to learn and practice TT3 with different methods. The selected study instrument was a TT3 score sheet. Scores before and after the test were recorded and analyzed using IBM SPSS Statistics. Result. The results of the data analysis showed that the pre-test scores obtained by both groups were quite similar because the same activities and amount of pre-test time were given. The post-test scores showed significant differences between both groups. Conclusion. Learning methods using observation techniques result in effective learning transfer because it saves time, subjects can witness TT3 demonstrations more often as well as teach many students.